Systematic Literature Review tentang Pemanfaatan Lingkungan Sekitar sebagai Sumber Belajar IPS untuk Menumbuhkan Kesadaran Sosial Siswa Sekolah Dasar - Nisa Audina Agustina; Rida Nazmi Farhani; Yona Wahyuningsih (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Social Studies (IPS) learning in elementary schools plays a crucial role in fostering students’ social awareness, which includes understanding social values, developing empathy, and participating responsibly in community life. However, in practice, Social Studies learning often remains theoretical and textbook-centered, making students’ learning experiences less meaningful and disconnected from real-life contexts. To address this issue, utilizing the surrounding environment as a learning resource offers an effective alternative by bringing real social situations into the learning process. This study aims to analyze the concepts, implementation, and impact of environmental utilization on enhancing elementary students’ social awareness. The research employed a Systematic Literature Review (SLR) method by reviewing relevant scholarly articles obtained from national and international databases such as Garuda, Google Scholar, and ScienceDirect, using the keywords “environment as a learning resource in Social Studies” and “students’ social awareness.” The findings reveal that the use of the surrounding environment as a learning resource promotes students’ critical thinking, empathy, and social concern through contextual and participatory learning experiences. Moreover, teachers play a pivotal role in designing project-based and field-observation activities that strengthen the internalization of social values. Therefore, Social Studies learning that integrates environmental resources is proven to be effective in shaping students’ social character from an early age and supports the realization of holistic, active, and life-oriented education.